2020
DOI: 10.1016/j.addma.2019.100920
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of PEEK/IF-WS2 nanocomposites for additive manufacturing: Simultaneous improvement in processing characteristics and material properties

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 29 publications
(35 reference statements)
1
44
0
Order By: Relevance
“…In a recent study, it has shown that interfacial interactions between fillers and matrix are considerably affected the mechanical features. The increment in mechanical features indicated a good interaction between the fillers and polymer matrix (Golbang et al, 2020). It was reported that mechanical features are also importantly influenced by the printing orientations and raster angles along with the filler material .…”
Section: Use Of Additivesmentioning
confidence: 88%
See 1 more Smart Citation
“…In a recent study, it has shown that interfacial interactions between fillers and matrix are considerably affected the mechanical features. The increment in mechanical features indicated a good interaction between the fillers and polymer matrix (Golbang et al, 2020). It was reported that mechanical features are also importantly influenced by the printing orientations and raster angles along with the filler material .…”
Section: Use Of Additivesmentioning
confidence: 88%
“…The sections printed with short glass fiber, CFR composites and other nano-fillers (such as calcium carbonate, vapor-grown carbon fibers, montmorillonite, tungsten disulfide, hydroxyapatite, silica, graphene, silicon carbide and multiwalled carbon nanotubes) showed improved mechanical, thermal and electrical features compared to those printed with standalone polymer substances (Papageorgiou et al, 2019;Parandoush and Lin, 2017). Besides, plasticizers and compatibilizers improve the processability of PEEK feedstock and its rheological properties, which directly affects the layer adhesion properties (Golbang et al, 2020;Wang et al, 2017).…”
Section: Use Of Additivesmentioning
confidence: 99%
“…PEEK is a thermoplastic with exceptionally high melting and glass transition temperatures due to its crystallinity and its stiff backbone interconnected by ketone and ether groups. It can be moulded by injection moulding and is used in nuclear plants, military, aerospace, chemical process equipment, oil‐well and bio applications 4–10 . PEEK has wide commercial application in electronic, telecommunication, healthcare and transportation industries (automotive, aeronautics and aerospace) and interest is continually growing in the ability to manufacture PEEK composites for electromagnetic interface (EMI) shielding and anti‐static applications to further enhance its applicability in these sectors 11–18 .…”
Section: Introductionmentioning
confidence: 99%
“…Levenhagen and Dadmun 21 effectively improved PLA fluidity by introducing a lower molecular weight PLA and the study showed that at 10 mol% loading of the PLA ( M w = 50 k) to a commercial PLA ( M w = 220 k), the maximum stress in the transverse orientation increased by 66% over that of the neat sample. Golbang et al 22 . demonstrated that the introduction of 2 wt% IF‐WS 2 to PEEK led to a reduction in melt viscosity of 25% and growth in storage modulus of about 60%.…”
Section: Introductionmentioning
confidence: 99%